PERINGKAT WEBSITE PERGURUAN TINGGI BERBASIS ANALISA HYPERLINK MENGGUNAKAN FACTOR ANALYSIS - Yuhefizar -; Mochamad Hariadi; Yoyon K Suprapto (Universitas Trunojoyo Madura, 2011)
Factor analysis is a multivariate method that is used to analyze correlation among indicator variables so that it can be mapped into some factors. Previous research has defined the importance of the role of a hyperlink from a website, but did not examine the most influential variables from some specified hyperlink variables. It is therefore necessary to obtain a factor analysis of the factors that affect the quality of a website from some specified hyperlink variables. Due to this analysis, top 25 university websites from webometrics of January 2011 edition rank have been selected as the research objects. The hyperlink data was obtained by utilizing two search engines, Google.com and Yahoo.com, then this hyperlink data were analyzed using factor analysis methods. The result should that the role of hyperlink total factor (0,254) and external hyperlinks factor (0,253) greatly affect the quality of a website on the review in terms of hyperlink perspective with analysis factor. This research also resulted in a new rank of university websites that can be used as one parametric for a good website's according to hyperlink analysis. The results of this analysis was tested at the level of correlation with parameters of size and visibility webometrics using Pearson correlation method with a highly significant result of 0.575.